Impairment of the type I interferon response by HIV-1: Potential targets for HIV eradication. (October 2017) - Sandstrom, Teslin S.; Ranganath, Nischal; Angel, Jonathan B.
Graphical abstract: Highlights: This review summarizes current knowledge of defects in the type I IFN response in primary cell models of HIV-1 infection. Type I IFN expression is upregulated during HIV-1 infection, but does not result in viral clearance. HIV-1 can interfere with the type I IFN response by impairing the function of antiviral, interferon stimulated genes. Despite these defects, therapeutic activation of type I IFN signalling may facilitate the clearance of the HIV-1 reservoir. Abstract: By interfering with the type I interferon (IFN1) response, human immunodeficiency virus 1 (HIV-1) can circumvent host antiviral signalling and establish persistent viral reservoirs. HIV-1-mediated defects in the IFN pathway are numerous, and include the impairment of protein receptors involved in pathogen detection, downstream signalling cascades required for IFN1 upregulation, and expression or function of key IFN1-inducible, antiviral proteins. Despite this, the activation of IFN1-inducible, antiviral proteins has been shown to facilitate the killing of latently HIV-infected cells in vitro . Understanding how IFN1 signalling is blocked in physiologically-relevant models of HIV-1 infection, and whether these defects can be reversed, is therefore of great importance for the development of novel therapeutic strategies aimed at eradicating the HIV-1 reservoir.